A Poisson type formula for Hardy classes on Heisenberg’s group - Lopushansky, O.V.; Oleksienko, M.V. (Carpathian Mathematical Publications, 2010)
The Hardy type class of complex functions with infinite many variables defined on the Schrödinger irreducible unitary orbit of reduced Heisenberg group, generated by the Gauss density, is investigated. A Poisson integral type formula for their analytic extensions on an open ball is established. Taylor coefficients for analytic extensions are described by the associated symmetric Fock space.